2018
DOI: 10.1002/cpt.1216
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Probes and Endogenous Biomarkers as Substrates for Transporter Drug‐Drug Interaction Evaluation: Perspectives From the International Transporter Consortium

Abstract: on behalf of the International Transporter ConsortiumDrug transporters can govern the absorption, distribution, metabolism, and excretion of substrate drugs and endogenous substances. Investigations to examine their potential impact to pharmacokinetic (PK) drug-drug interactions (DDIs) are an integral part of the risk assessment in drug development. To evaluate a new molecular entity as a potential perpetrator of transporters, use of well characterized and/or clinically relevant probe substrates with good sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
225
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(230 citation statements)
references
References 102 publications
(159 reference statements)
2
225
0
3
Order By: Relevance
“…Therefore, in the RSV‐RIF study, RIF likely affected the first‐pass hepatic extraction of RSV resulting in a bigger increase in RSV plasma concentration. The percent change in plasma concentrations of CPI, CPIII, TBILI, and DBILI in our study are comparable to those observed in humans following RIF administration and cynomolgus monkeys after CsA administration (100 mg/kg p.o.) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, in the RSV‐RIF study, RIF likely affected the first‐pass hepatic extraction of RSV resulting in a bigger increase in RSV plasma concentration. The percent change in plasma concentrations of CPI, CPIII, TBILI, and DBILI in our study are comparable to those observed in humans following RIF administration and cynomolgus monkeys after CsA administration (100 mg/kg p.o.) .…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, in the RSV-RIF study, RIF likely affected the firstpass hepatic extraction of RSV resulting in a bigger increase in RSV plasma concentration. The percent change in plasma concentrations of CPI, CPIII, TBILI, and DBILI in our study are comparable to those observed in humans following RIF administration [35][36][37] and cynomolgus monkeys after CsA administration (100 mg/kg p.o.). 38 These percent changes are greater for the biomarkers than those for blood [ 11 C]RSV AUC 0-30 minutes because the biomarkers likely have greater fraction transported via OATPs than RSV (which is a substrate of both OATPs and NTCP).…”
Section: Discussionsupporting
confidence: 87%
“…In the transporter field, great progress has been made to identify clinical relevant biomarkers as substrates for various transporters, such as CPI (coproporphyrin I) and CPIII (coproporphyrin III) for the OATPs, creatinine and N 1 ‐methylnicotinamide for OCT2/MATE, and taurine for OAT1 (Chu et al, ). Several transporter biomarkers appear to be more sensitive and robust than the enzyme biomarkers in the clinic.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%
“…Transporters with only mRNA or limited data are depicted in brown circles, whereas those that have both gene expression and protein abundance data are depicted in green circles. (Adapted/modified from Brouwer et al and Chu et al …”
Section: Ontogeny Of Membrane Transportersmentioning
confidence: 99%
“…Transporters with only mRNA or limited data are depicted in brown circles, whereas those that have both gene expression and protein abundance data are depicted in green circles. (Adapted/modified from Brouwer et al14 and Chu et al67 ) Noteworthy, the localization of OATP2B1 remains questionable. Future investigation is needed to ascertain if its localization is subject to developmental changes.…”
mentioning
confidence: 99%